Adaptasi Motif Jong Sarat dalam penghasilan karya pointillism - Siti Hamizah, Matali (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This study is about the application Jong Sarat motive in art of Pointillism. The researchers also show that cultural object become symbolizes cultural of Malay Brunei ethnicity. Researchers also wanted to identify Jong Sarat motive and analyzing the potential of matchsticks in the production of Pointillism. Researchers refer to several artists with their work, scientific book related to woven fabric of Brunei and researches goes to Training Center of Art and Craft of Brunei for the validity of information. Researchers used matchsticks as the main media in the production of personal work. Finally, the researcher found a matchstick has very high potential to produce this work because it is round and closer to the concepts of Pointillism. (keyword : Jong Sarat, Pointillism, matchstick, Malay Brunei )